Sensory Attributes and Consumer Acceptability of 12 Microgreens Species - Francesco Caracciolo; Christophe El-Nakhel; Maria Raimondo; Marios C. Kyriacou; Luigi Cembalo; Stefania De Pascale; Youssef Rouphael (Agronomy, 2020)
Microgreens are gaining increasing recognition among consumers, acclaimed for their freshness and health promoting properties associated with densely fortified secondary metabolites. These immature greens enhance human diet and enrich it with sharp colors and flavors. While numerous species are being tested for agronomic and nutritional suitability, consumer acceptance of appearance, texture, and flavor is critical for the microgreens’ marketplace success. This study investigates whether sensory attributes and visual appearance affect consumer preference for microgreens and their willingness to consume them. By means of a consumer test, the sensory attributes of 12 microgreens species were evaluated, wherein a partial least squares structural equation model was developed to link sensorial attributes to willingness to eat the product. The results showed that although visual appearance of the microgreens was largely appreciated, consumer acceptance overall was mainly determined by flavor and texture. In particular, the lower the astringency, sourness, and bitterness, the higher the consumer acceptability of microgreens. Among the 12 examined species, mibuna and cress scored the lowest acceptance by consumers, while Swiss chard and coriander were the most appreciated, being therefore good candidates to be introduced in Western country markets. In addition, both Swiss chard and coriander have been identified by previous literature as good dietary source of phenolic antioxidants.